Enkele kwelvrae oor die grondwetlike beskerming van die reg op godsdiensvryheid - Malherbe, R (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
In this contribution the right to freedom of religion is briefly and by way of introduction discussed with reference to the bearers of the right, the conduct and interests protected by the right, the binding effect of the right, and the requirements for the lawful limitation of the right. The application of the right is discussed with reference to several recent court judgments, after which a few nagging questions are put forward about the constitutional protection of the right to religious freedom. First, the non-entanglement principle, in terms of which a court of law is supposed not to intervene in doctrinal issues, is discussed and applied to South African law. The view is put forward, inter alia with reference to certain court judgments, that the doctrine applies in South Africa, on condition that churches indeed have a clear and definite view on a particular matter. Secondly, the policy of the government relating to religion in education is analysed and the conclusion is made that the policy seeks to (a) enforce a state determined secular worldview upon pupils, and (b) restrict the constitutional right to conduct religious observances in school, and that it thus violates the right to freedom of religion. Finally, it is stated that religion remains a sensitive issue which should be treated in a spirit of tolerance. Churches have the responsibility to act as watchdogs over the protection of religious freedom and should speak out whenever the right is threatened. If they don’t, their influence in a secularising world will wane. If they do, they will have the right, authority and legitimacy to combat effectively contemporary threats to religious freedom.